Network pharmacology of black cumin (Nigella sativa L.) as a candidate of OMAI in colorectal cancer: in silico study - Firzannida Firzannida; Sakti Bagaskara; Savana Sonia Savira; Aufa Fadnurrahim; Siti Rofida (Indonesian Journal of Biotechnology, 2022)
Colorectal cancer is the third most common cancer globally and the second leading cause of cancer‐related deaths. The management of colorectal cancer requires consideration of various factors due to the non‐selectivity of drugs, meaning that highly effective treatment with lower side effects is needed. Black cumin (Nigella sativa L.) contains thymoquinone and various other metabolites with potential as anticancer effects. The involvement of various genes and the difficulty of drug development have led to a ashift in the drug development paradigm towards plant‐based medicine that is both multicomponent and synergistic in supporting the resulting pharmacological effects. Network pharmacology can predict the synergistic effect of a multicomponent approach. This study aimed to predict the network pharmacology of black cumin as a candidate for OMAI (“Obat Modern Asli Indonesia”, Indonesian‐origin modern medicine) in colorectal cancer. This research was an in silico study using various ethnobotanical databases and software. The results show that seven metabolites in black cumin are correlated with ten surface receptor proteins, 30 intracellular proteins, and mechanisms involving six colorectal cancer signaling pathways. This result indicates that Nigella sativa L. has potential in OMAI and can be a reference for the development of cancer treatment, especially for colorectal cancer.